Midline catheter as effective device in healthy allogeneic donors and patients without an adequate peripheral venous access for HPC collection by apheresis: Preliminary experience at IEO. (June 2020) - Caime, Alessandro; Piredda, Alessio; Lucchetti, Bruno; Magarò, Antonio; Zencovich, Claudia; Clerici, Margerita; Laszlo, Daniele
Abstract: Collection of HPC by apheresis requires adequate venous access for inflow and for outflow. The use of midline has never been reported in this setting. We prospectively analyzed the use of midline for performing apheresis on 3 healthy donors and 3 adults patients requiring autologous transplantation. A total of 8 polyurethane midlines, with an external diameter of 5 French, was inserted (2 midlines in both arms in 2 healthy donors) by our PICC team the day before apheresis and removed at the end of target collection. Mean flow rate was 35 ml/min. Target cellular dose was reached in all patients / donors with a maximum of 2 procedures without any complications. Midline is effective and safe for HPC collection either in donors or patients avoiding the placement of a central venous catheter.